2023
DOI: 10.3390/children10040717
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-Up of a Child with Non-Syndromic Oligodontia from before the Primary Dentition Stage: A Case Report

Abstract: Background: Congenital absence of teeth is a major dental abnormality in pediatric dentistry and the absence of six or more teeth is defined as oligodontia. Few reports of patients with non-syndromic oligodontia without systemic disease have continued dental follow-up from an early age. Methods: We performed the five-year follow-up from before the eruption of the primary dentition of a Japanese child with non-syndromic oligodontia and analyzed changes in dental arch growth. Results: At the oral examination at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Dental anomalies include abnormal tooth counts, morphology, size, and eruption times [1][2][3][4]. Congenital types are inherited and have a genetic basis, developmental types occur at the tooth formation stage, and acquired anomalies occur after tooth development [5].…”
Section: Introductionmentioning
confidence: 99%
“…Dental anomalies include abnormal tooth counts, morphology, size, and eruption times [1][2][3][4]. Congenital types are inherited and have a genetic basis, developmental types occur at the tooth formation stage, and acquired anomalies occur after tooth development [5].…”
Section: Introductionmentioning
confidence: 99%
“…We found that congenital absence after chemotherapy occurs with high frequency in premolar and 2nd molar, and microdonts occur with high frequency in premolar. Long-term follow-up is necessary because patients with dental abnormalities sometimes need prosthodontic or conservative treatment [27]. Furthermore, continuous dental support after the treatment is completed leads to better general oral health, which improves patients' quality of life [28].…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary central incisors have a significant impact on facial attractiveness [5] . Impaction of maxillary central incisors has the potential to cause speech problems; especially in pronouncing “S” [6] . Tipping of the adjacent teeth, space deficiency, and midline deviation were reported [7] .…”
Section: Introductionmentioning
confidence: 99%